1979
DOI: 10.1111/j.1365-2222.1979.tb01530.x
|View full text |Cite
|
Sign up to set email alerts
|

IgE and IgG4 subclass in atopic families

Abstract: Raised levels of IgG4 were present in twelve (35%) of thirty-four asthmatic children and raised levels of IgE in twenty-three (68%). Eighteen of 104 first degree relatives also had raised levels of IgG4, thirteen had no history ofatopic disease and nine failed to give positive skin reactions to Dermatophagoides pteronyssinits or to mixed grass pollens. Fifteen relatives had raised IgE, five without symptoms.No relationship was noted between either raised levels of IgE or IgG4 and infant feeding. Although these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
2

Year Published

1983
1983
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 7 publications
4
24
2
Order By: Relevance
“…Since the incidence of low IgG4 does not alone seem to account for the pre viously observed sex difference [21], we suspect that our results are related to the strict selection of patients on serological grounds whereas in previous studies randomized 'healthy' persons were investigated [21][22][23], which might cause bias from men prone to develop atopy. Moreover, in one of these previous randomized studies the observed sex difference in lgG4 was also accompanied by one in IgE [22], Our finding of raised IgG4 levels among patients considered atopic on serological grounds is in agree ment with previous data on both atopic adults and at opic children [28][29][30]. We also confirm the reports of very high IgG4 levels in patients with atopic dermati tis [31,32] and lymphatic filariasis [11] and we add an other parasitic disease, onchocerciasis, to the list of helminthic diseases besides schistosomiasis [10] show ing elevated lgG4.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Since the incidence of low IgG4 does not alone seem to account for the pre viously observed sex difference [21], we suspect that our results are related to the strict selection of patients on serological grounds whereas in previous studies randomized 'healthy' persons were investigated [21][22][23], which might cause bias from men prone to develop atopy. Moreover, in one of these previous randomized studies the observed sex difference in lgG4 was also accompanied by one in IgE [22], Our finding of raised IgG4 levels among patients considered atopic on serological grounds is in agree ment with previous data on both atopic adults and at opic children [28][29][30]. We also confirm the reports of very high IgG4 levels in patients with atopic dermati tis [31,32] and lymphatic filariasis [11] and we add an other parasitic disease, onchocerciasis, to the list of helminthic diseases besides schistosomiasis [10] show ing elevated lgG4.…”
Section: Discussionsupporting
confidence: 81%
“…Although some previous investigators have failed to see this parallellism [22], perhaps be cause of the population sample characteristics, others have noticed it [10]. Besides their prominence in atopic and helminthic diseases, a whole array of simi larities seems to exist between these two immunoglob ulins; they tend to run in families [29], their concentra tions increase very slowly in infancy to reach adult lev els in puberty [33], they both show seasonal variations in the antibody response to pollen allergens [7], nei ther of them responds when lymphocytes are stim ulated in vitro by Pokeweed mitogen [34], and IgG4 deficiency is often accompanied by an IgE deficiency [13]. Even though the reason for this relationship be tween IgE and IgG4 might be due to polyclonal B cell activators in some instances [35], this seems highly un likely on a general basis.…”
Section: Discussionmentioning
confidence: 99%
“…In atopic patients an imbalanced IgG subclass pattern with increased IgG4 is common [9,12,18,19]. In normal individuals increased IgG4 is associated with the G2m(n) allotype [22], In patients with atopic eczema those who possessed the G2m(n) allotype were found to have the highest levels of milk-and egg-specific IgG4 [19,20], Patients with increased IgG4 together with increased IgE have been reported to have more severe manifestations of their atopic disease [9].…”
Section: Discussionmentioning
confidence: 99%
“…IgG4 represents about 3% of serum IgG in healthy individuals [1], but in atopic patients, particularly those with eczema, levels can be markedly elevated [2][3][4], A raised serum level of IgG4 is of interest be cause it has been suggested that this IgG subclass might have anaphylactic properties. Thus, the pres ence of receptors for IgG4 on human basophils has been indirectly demonstrated by showing that a mono clonal anti-IgG4 antibody can stimulate peripheral blood leucocytes to release histamine [5], It has not been possible, however, to reproduce this effect when leukocytes of patients with allergen-specific IgG4 were challenged with the relevant allergen [6], This is probably due to insufficient cross-linking of cellbound lgG4 with the allergen as lgG4 might act as a monovalent antibody [7], It is not surprising, there fore, that allergen-specific IgG4 is often found in sera of individuals with no apparent clinical sensitivity to that allergen [8][9][10],…”
Section: Introductionmentioning
confidence: 99%